(untitled) (Fiep Bulletin - online, 2014)
The laser of low potency induces the cellular biostimulation that could cause increase of the mitochondrial breathing and synthesis of ATP, to accelerate the cicatrization of wounds, to promote the regeneration of the skeletal muscle, to reduce the inflammatory answer and to stimulate angiogenic process. The objective of this study was to analyze the effects of the two irradiation doses of treatment with low level laser, in the analgesia and edema of rats submitted to the experimental lesion of the muscle lateral gastrocnemius. Males rats Wistar (n=20) were used, randomly distributed in three groups, being: GC- injuried animals and agreements with turned off equipment (sham); G10- injuried animals and irradiated with dose of 10 J/cm², 670 nm; G20- injuried animals and irradiated with dose of 20 J/cm², 670 nm. For the production of the experimental lesion, 0,1 ml of formalina 5% was introduced, in the three groups, in the lateral gastrocnemius muscle girth. The evaluation of the pain happened through the Time of Elevation of the Paw (TEP), and the edema was evaluated with aid of metallic caliper, both evaluations happened before the lesion, soon after the lesion, after the treatment, 2, 8 and 24 hours after the lesion. The results showed significant increase of TEP and of the edema, in every moment evaluated after the induction of the lesion. It is ended that laser, in the used parameters, did not produce decrease in the pain and edema in animals submitted to the muscular lesion with injection of formalina 5%.